Media Development with Chinese Characteristics (Global Media Journal - German Edition, 2015)
Chinese authorities often frame their activities in the development sector as distinctive from those pursued by Western donors by stressing that they are not seeking to export a specific model but simply to help countries reach their potential. This demand-driven approach has applied to old and new development areas, from education to Information and Communication Technologies (ICTs), and has appeared fairly consistent across countries. This pledge, however, has not meant that Chinese aid is neutral or without significant political implications. China’s concessionary loans and support to development projects have tended to shift balances of power by favouring certain actors over others and have challenged existing development paradigms, revitalizing ideas of the developmental state. Building on fieldwork conducted in Ghana, Ethiopia, and Kenya this article explains to which extent China’s entrance in the media and telecommunication sector actually challenges the dominant, Western-driven approaches to media development, promoting a state centred vision of the information society.
Keywords: media development; China-Africa relations; conceptions of the information society; African media